1987
DOI: 10.1111/j.1469-8137.1987.tb04795.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation (Acetylene Reduction) by Forest Legumes: Sensitivity to Pre‐harvest and Assay Conditions

Abstract: SUMMARYThe effects of enwronmental and methodological factors on acetylene reduction by nodules of Acacia pulchella R.Br., Kennedia coccinea Vent, and K. prostrata R.Br. grown in pots were studied.The time course of acetylene reduction, measured for each species during assays lasting up to 3 h, showed that there was an initial lag phase before maximum rates were reached and that rates then declined rapidly. This decline in activity was less marked for K. prostrata than for the other two species. Rates of acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
1
0
0
1
Order By: Relevance
“…These vesicles are in charge of protecting the nitrogenase complex. These actinobacteria have been extensively reported by several authors [59][60][61], due to its fixation characteristics that have been confirmed by acetylene reduction method [62][63][64]. The morphology of the bacteria cultured in our laboratory facilities using Nfb media did not display any similarity with Frankia sp, since different microscopic descriptions such as long and short filaments, tortuous or spiral-shaped filaments were found.…”
Section: Non-symbiotic Nitrogen Fixationsupporting
confidence: 61%
“…These vesicles are in charge of protecting the nitrogenase complex. These actinobacteria have been extensively reported by several authors [59][60][61], due to its fixation characteristics that have been confirmed by acetylene reduction method [62][63][64]. The morphology of the bacteria cultured in our laboratory facilities using Nfb media did not display any similarity with Frankia sp, since different microscopic descriptions such as long and short filaments, tortuous or spiral-shaped filaments were found.…”
Section: Non-symbiotic Nitrogen Fixationsupporting
confidence: 61%
“…Douze semaines après inoculation, les plantules sont déterrées et leur système racinaire est lavé à l'eau du robinet et rincé avec de l'eau distillée stérile. Les nodules des plants d'un même pot sont excisés et leur pouvoir fixateur d'azote est déterminé par la mesure de leur ARA (activité réductrice de l'acétylène (C 2 H 2 ) en éthylène (C 2 H 4 )) selon la méthode préconisée par Grove et Malajczuk (1987). Les nodules sont alors mis à sécher à 65 °C pendant 96 heures et leur poids sec est déterminé.…”
Section: Tests De Nodulationunclassified